Impact of COVID-19 on Disease Self-management Among Patients With Advanced CKD: A Qualitative Study - Jia H. Ng; Candice Halinski; Devika Nair; Michael A. Diefenbach (Kidney Medicine, 2023)
Rationale & Objective: Patients with advanced chronic kidney disease (CKD) and their care partners experienced decreased access to care, and worse physical and emotional health during the coronavirus disease 2019 (COVID-19) pandemic. Few studies have explored how COVID-19-related challenges affect disease self-management among those with advanced CKD and their care partners. Leventhal’s self-regulation model offers a comprehensive framework for understanding disease self-management through the interplay of cognitive beliefs, emotional reactions, and social influences. The study aimed to examine the impact of COVID-19 on self-management activities among patients with CKD and their care partners. Study Design: Qualitative study. Setting & Participants: Adults with advanced CKD, including dialysis and transplant recipients, and their care partners. Analytical Approach: Thematic analysis Results: Among 42 participants, 12 had stage 4 CKD, 5 had stage 5 CKD, 6 were receiving in-center hemodialysis, 5 had a kidney transplant, and 14 were care partners. We identified 4 patient-related themes with corresponding subthemes related to the impact of COVID-19 on self-management: 1) cognitive understanding that COVID-19 is an additional health threat to existing kidney disease; 2) heightened anxiety and vulnerability driven by perceived risk; 3) coping with isolation through virtual interactions with health care services and social circles; and 4) increased protective behaviors to maximize survival. Three care partner-related themes emerged: 1) hypervigilance in family care and protection; 2) interaction with the health system and adaptations to self-management; and 3) increased intensity in the caregiving role to facilitate patient self-management. Limitations: The qualitative study design limits the ability to generate generalizable data. Grouping patients with stage 3 and 4 CKD, in-center hemodialysis, and kidney transplants together limited our ability to examine self-management challenges specific to each treatment requirement. Conclusions: When faced with the COVID-19 pandemic, patients with CKD and their care partners experienced heightened vulnerability and thus increased cautionary activities to maximize survival. Our study provides the groundwork for future interventions to help patients and care partners live with kidney disease during future crises. Plain Language Summary: During the coronavirus disease 2019 pandemic, patients with advanced chronic kidney disease (CKD) and their care partners faced reduced access to care and worsening physical and emotional health. Our study aimed to understand how coronavirus disease 2019-related challenges affected disease self-management for these individuals using Leventhal’s self-regulation model. We conducted a qualitative study with 42 participants, including patients with various stages of CKD and their care partners. Our findings revealed that both patients and care partners experienced heightened vulnerability during the pandemic, leading to increased protective behaviors and intensified caregiving roles. This suggests that individuals self-manage existing CKD based on their cognitive and emotional representations and interpersonal processes. This lays the foundation for future interventions for self-management for kidney disease during times of crisis.